Kurikulum taman kanak-kanak (TK) : garis-garis besar program pengembangan (GBPP) bidang pengembangan pendidikan moral Pancasila (Departemen Pendidikan dan Kebudayaan, 1986)
Development programs for curriculum for kindergartens in Indonesia with special reference to Pancasila education.